2022
DOI: 10.1093/braincomms/fcac277
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Y chromosome haplogroups in Parkinson’s disease

Abstract: Parkinson's disease is a complex neurodegenerative disorder that is about 1.5 times more prevalent in males than females. Extensive work has been done to identify the genetic risk factors behind Parkinson's disease on autosomes and more recently on chromosome X, but work remains to be done on the male specific Y chromosome. In an effort to explore the role of the Y chromosome in Parkinson's disease we analyzed whole genome sequencing data from the Accelerating Medicines Partnership - Parkinson's disease initia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Recent GWAS studies have explored the causation behind gender differences in European cohorts. However, they have been unable to find any conclusive argument from the analyses of the autosomal and sex chromosomes [ 88 90 ]. A comprehensive meta-analysis of several diverse cohorts also did not offer any leads on gender differences [ 91 ].…”
Section: Challenges Of Understanding Genome-wide Association At a Mol...mentioning
confidence: 99%
“…Recent GWAS studies have explored the causation behind gender differences in European cohorts. However, they have been unable to find any conclusive argument from the analyses of the autosomal and sex chromosomes [ 88 90 ]. A comprehensive meta-analysis of several diverse cohorts also did not offer any leads on gender differences [ 91 ].…”
Section: Challenges Of Understanding Genome-wide Association At a Mol...mentioning
confidence: 99%
“…Recently, a large-scale association study was reported that examined the association between Y haplogroups and the risk of Parkinson's disease. Grenn et al identified haplogroups, variants, and gene expression patterns potentially associated with Parkinson's disease risk in males using multiple large cohorts [Grenn et al, 2022] (shown in Table 1). They analyzed blood-based RNA sequence data obtained from the Accelerating Medicines Partnership-a Parkinson's disease initiative including 1,020 samples and RNA sequence data obtained from the North American Brain Expression Consortium including 171 samples to identify Y chromosome genes differentially expressed in cases and controls with specific haplogroups and specific tissues.…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
“…One study of Parkinson’s disease explored the association with Y chromosome haplogroups and single Y chromosome variants, albeit they did not find significant associations, which the authors note could be in part due to a large portion of the chromosome (30 Mb) being difficult to assess given its heterochromatic nature and the presence of repeats. 76 Similarly, no significant associations with multiple sclerosis have yet been identified with more recent Y chromosome data. 59…”
Section: Introductionmentioning
confidence: 95%